The Role of Clouds in Arctic Climate - Sundermann, Hannah (UiT Norges arktiske universitet, 2024)
Anthropogenic climate change is causing the Arctic to warm faster than any other region on Earth, a phenomenon also known as Arctic amplification. The warming and its consequences induce, amongst other things, a change in clouds, impacting their role in the Arctic climate by introducing a feedback. Clouds play an important role in the global radiation budget. They cool the surface by reflecting incoming shortwave radiation and warm it by absorbing and re-emitting longwave radiation. While the cooling effect outweighs the warming on a global mean, clouds warm the Arctic surface. The precise impact of clouds on the Arctic climate, particularly in global climate models, remains uncertain and is subject of ongoing research. This thesis studies the sensitivity of the Arctic climate to local changes in microphysical cloud properties using the Community Earth System Model 2.1.3 (CESM). First-order impacts of cloud alterations resulting from climate change were studied. Therefore, a simulation with clouds from a 2xCO2 environment within a climate model set to pre-industrial CO2 levels was conducted. These changes were only implemented concerning the radiation transfer scheme of CESM. The results show a net warming effect in winter and a cooling effect in summer, with the warming effects predominating. Additionally, dedicated numerical experiments were conducted to investigate how variations in droplet size distribution, ice crystal sizes, liquid and ice water paths, and cloud fraction influence Arctic temperature, sea ice extent, and radiation fluxes. These experiments aimed to evaluate the model's accuracy in representing cloud microphysical parameters and their alignment with established theoretical frameworks.